2021
DOI: 10.1007/s10900-021-00964-7
|View full text |Cite
|
Sign up to set email alerts
|

Firearm Suicides in the Elderly: A Narrative Review and Call for Action

Abstract: Firearm suicides are one of the leading causes of death for older Americans. The purpose of this review is to explore the risk factors associated with suicides in the elderly, provide an overview of the epidemiology of firearm-related suicides in older Americans, and explore methods of preventing firearm suicides in the elderly. The vast majority (70 %) of elderly suicides in the U.S were committed using a firearm. Elderly firearm suicides have increased by 49 % between 2010 and 2018, disproportionately affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Our analysis shows that over the past decade, among Hispanic adults, firearms have surpassed all other means of suicide in males, and among females, they are now the second most common cause of suicidal deaths. This may reflect the growing trend of suicides with firearms across all racial and age groups [ 4 7 , 42 , 52 , 53 ]. Firearm access and ownership among Hispanics has also been increasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis shows that over the past decade, among Hispanic adults, firearms have surpassed all other means of suicide in males, and among females, they are now the second most common cause of suicidal deaths. This may reflect the growing trend of suicides with firearms across all racial and age groups [ 4 7 , 42 , 52 , 53 ]. Firearm access and ownership among Hispanics has also been increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our analysis is primarily descriptive using a cross-sectional design, limiting the ability to comment on causal factors associated with suicides. Third, WISQARS does not have key sociodemographic information such as marital status, education, income, immigration status, birth country, and others that could provide an opportunity for a more nuanced analysis [ 3 , 4 , 21 , 53 ]. Finally, a group of scholars has suggested that the recorded levels of Hispanic suicides may be lower than reality due to possible misclassification by approximately 17% [ 3 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“… 8 These stress-inducing variables of life can accumulate, with many elderly adults reporting feelings of loneliness and isolation. 9 Loss of a job or retirement with subsequent reliance on social security income has been cited as a major stressor in older adults as the loss of financial resources causes individuals to perceive themselves as a burden to family members and society. 10 This is further compounded in individuals who identify themselves as their job, as the loss of their job further exacerbates lack of kinship and inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that major depressive disorders are present in approximately 50% of the suicide victims, and that financial, relationship, and other outside stressors are frequently present in these individuals 8. These stress-inducing variables of life can accumulate, with many elderly adults reporting feelings of loneliness and isolation 9. Loss of a job or retirement with subsequent reliance on social security income has been cited as a major stressor in older adults as the loss of financial resources causes individuals to perceive themselves as a burden to family members and society 10.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in developing countries (such as Venezuela, Lesotho, Central African Republic, Eswatini, Mozambique) where low mortality rates from suicide by firearm were recorded at the beginning of the observed period, significantly higher rates were recorded in 2019 for both sexes. Marked geographic variations in mortality rates of suicide by firearm could be explained by different prevalence of the main risk factors (such as some socio-demographic characteristics, firearms ownership and availability, large alcohol consumption, comorbidity, etc), and variations in suicide prevention [ 2 , 4 , 32 , 33 ]. Besides, it is always a question whether the differences in mortality of suicide by firearm are real or partialy reflect variations in data quality worldwide, in the process of registering causes of death or under-reporting [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%